Designing the Visual Identity of Malay Cultural Arts Based on Generation Z Visual Preferences: A Design Thinking Approach - Widiya Lestari Harahap; Tommy Andrea Gunawan; Clarita Novia; Enzi Juro; Yaya Olivia (Judikatif: Jurnal Desain Komunikasi Kreatif, 2026)
The visual identity of Malay cultural arts faces a pressing relevance challenge in the digital era, particularly among Generation Z who have grown up with modern, minimalist, and fast visual preferences. This study aims to map the visual preferences of Generation Z toward Malay cultural arts and, based on those preferences, to formulate a conceptual framework for designing an adaptive Malay visual identity through a Design Thinking approach. The authors employed a descriptive quantitative survey, administered online to 51 respondents aged 17 to 27 years, complemented by thematic analysis of open-ended answers. The survey instrument was structured following the first three stages of Design Thinking, namely empathize, define, and ideate, hereafter called the diagnostic stages. Instrument reliability was assessed using Cronbach’s alpha, and the overall scale of 20 items reached α = 0.838, which is considered good for an exploratory descriptive study. The results show that Generation Z perceives the current visual representation of Malay culture as conventional and dated, with 70.6% rating it as either conventional or behind the times. The digital engagement disposition recorded the highest construct mean (M = 4.02 on a 5-point scale), and the statement that respondents grasp cultural values more easily through creative visuals than through long text reached the highest single mean (M = 4.29). In other words, Generation Z is willing to engage with Malay culture, provided that it is delivered in a visual and short-format manner. However, the preference for neutral colors recorded the lowest mean (M = 3.41), and the qualitative data confirmed that respondents want the Malay color palette and motifs to be retained rather than removed. Thus, the authors propose the Hybrid Malay Visual Identity Framework, hereafter called HMVIF, which integrates three dimensions: the cultural dimension, the contemporary aesthetic dimension, and the digital communication dimension. This framework is expected to serve as a practical reference for designing a Malay cultural visual identity that is modern, communicative, and rooted in local values, especially in the Riau Archipelago. Keywords: Malay culture, visual identity, Design Thinking, Generation Z, visual communication design